First, Second and Finally Third Order Understandings of Lithuanian National Identity: an Anthropological Approach - de Munck, Victor C. (Sociologija. Mintis ir veiksmas, 2007)
The term ‘national identity’ implies homogeneity, but field research shows that the members of a nation are very heterogeneous in their conceptions of their own national identity. How then can we speak of a national identity when there is significant diversity among the members of a nation? I rely on concepts of ‘first order’ and ‘second order’ components of identity to resolve this question. First order concepts are constructed from the top down by the cultural elite and second order concepts are precipitates of behavior from the bottom up through personal experiences. I also rely on the importance of situated knowledge as the way identity is understood in social practice. Situated knowledge used by ego in social interactions. Situated knowledge creates a common national (or cultural) identity when ego knows not only that alter knows what ego knows but that ego “knows that alter knows that ego knows that alter knows.” It is this third order “Knowing” that creates, expresses, and maintains a national identity that is actually practiced in everyday life. I conclude by noting that a socially just inclusive model of national identity has to be based on this “third order” understanding of national identity.